COMMUNITY MODELS IN REHABILITATION: A COMPREHENSIVE OVERVIEW - Mudasir Ahmad Sofi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Rehabilitation is a multifaceted process aimed at enabling individuals with disabilities or impairments to achieve and maintain optimal physical, sensory, intellectual, psychological, and social functional levels. This research paper explores various community-based rehabilitation (CBR) models, their theoretical underpinnings, practical applications, benefits, challenges, and the evidence supporting their effectiveness. By examining successful case studies and identifying key components of effective community rehabilitation programs, this paper provides insights into how these models can be implemented and scaled to improve outcomes for individuals and communities alike.